Efficacy and safety of nitazoxanide based quadruple regimen as first line therapy for treating Helicobacter pylori infected naïve patients - Amro M Hassan; Muhammad Abdel-Gawad; Maie M Mahmoud; Emad Abdelrazzak; Safwat S Sawy; Mohamed A Sayed; Rasha Maree O Ali; Waleed S EL-Nasser; Mohamed Ahmad Younes Hussein; Mohamed Ramadan Izzaldin; Mohammed F Mohammed (Journal of Infection in Developing Countries, 2025)
Background: Eradication of H. pylori is a challenging issue in many parts of the world including Egypt.